Analisis kesalahan penggunaan huruf kapital pada karangan narasi peserta didik kelas V sekolah dasar - Kisma Arrum Maharatri; Siti Wahyuningsih; Suharno Suharno (Universitas Sebelas Maret, 2021)
This study aims to determine the form of capital letters errors in the narrative essay of the fifth grade students of SD Negeri 3 Sempor and the underlying factor in the misuse of capital letters. This study is against the background of errors that learners often use in capital letters. The study used qualitative descriptive methods aimed at analyzing the misuse of capital letters in the country's 3 sempor class v student narrative. The subject of this study is a 24-student v-class student and cass V teacher of SD Negeri 3 Sempor. The study uses data-collection techniques of documentation, interviews, and observation. Data analysis uses interactive data analysis techniques with data gathering, data reduction, data presentation, and deduction drawing. The validity of data on this research uses technical triangulation and source triangulation. The results of this study have been found misusing capital letters in the narrative of 3rd sempor country's vice student v. The error covers six indicators of error at the beginning of the sentence as many as 59 errors, errors in the name of as many as 4 errors, errors in the name of the day as 8 errors, errors in the geography name as 21 errors, and errors in the title of 21 errors. The most common mistake was the start of a sentence of 56% and the least amount of error on a person's name of 4%. A factor behind the misus of capital letters is that learners lack an understanding of the code of capital letter writing.